2004
DOI: 10.1111/j.1423-0410.2004.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat sensitivity of a SARS‐associated coronavirus introduced into plasma products

Abstract: If by rare chance SARS-CoV contaminates source plasma, there should be no or only minor risk of this virus infection, due to sufficient inactivation by the 60 degrees C 10 h liquid heating step, although we must pay attention to the composition used for blood product preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 3 publications
2
45
0
1
Order By: Relevance
“…We found that 90 minutes at either 56 or 65°C was necessary to inactivate the virus. 6 Yunoki and associates 21 examined the sensitivity of SARS-CoV to 60°C heat and found that the different protein compositions of the samples tested affected the time necessary, yet all samples were inactivated to the limit of detection by 1 hour. Additionally, Rabenau and coworkers 22 tested heat inactivation of SARS-CoV at 56°C for 30 minutes and determined that the presence of 20 percent fetal calf serum protected the virus.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 90 minutes at either 56 or 65°C was necessary to inactivate the virus. 6 Yunoki and associates 21 examined the sensitivity of SARS-CoV to 60°C heat and found that the different protein compositions of the samples tested affected the time necessary, yet all samples were inactivated to the limit of detection by 1 hour. Additionally, Rabenau and coworkers 22 tested heat inactivation of SARS-CoV at 56°C for 30 minutes and determined that the presence of 20 percent fetal calf serum protected the virus.…”
Section: Discussionmentioning
confidence: 99%
“…In-house studies of methods to inactivate coronaviruses in plasma and platelet concentrates focused mainly on heat and solvent/detergent (S/D) treatment. Usually, 60°C for 15-30 minutes is enough for reduction of SARS-CoV from plasma without cells [49], and inactivation could be achieved by 60°C for 10 hours for plasma products [52]. In the other study, heating at 56°C for 25 minutes could reduce more than 4 log 10 TCID 50 /mL of MERS virus [53].…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 96%
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…The changes in weather alone would not necessarily decrease numbers of confirmed cases during the whole epidemic, but warm and humid weather could make SARS-CoV-2 less transmissible and less stable, provoking a break in the chain of transmission, and hence diminishing the contagious force of the disease [5]. Ancient [1,4,5] studies, as well as characteristics of the covid-19 disease compared to past corona infections like the SARS one [3,[6][7][8], suggest that the spread of covid-19 could diminish in warm weather, particularly at the start of the epidemic, and may have a low temperature threshold under which it could spread fastest. These seasonal changes could occur in exactly the same way as for other pathogens, like the common cold or influenza [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%